Evaluasi Literatur Tugas Akhir Mahasiswa Prodi D-3 Perpustakaan di Ruang Baca FKIP UNTAN Periode 2017-2020 - Dea Agustianita; Atiqa Nur Latifa Hanum (Institut Agama Islam Negeri (IAIN) Curup, 2022)
This research discusses citation analysis that can be used as a tool for evaluating library collections. The aim is to investigate the type, author, half-life, and availability of literature being cited and also the different numbers of certain literature used in the final assignments of D-3 Library students. The research method used is descriptive quantitative with the research population of all final assignments of D-3 Library students from 2017-2020, amounting to 71. The writer used a documentation techniques to collect the data. The results show that the literature cited books are 686 (68.39%), theses/thesis/final assignments are 156 (16%), journals are 72 (7.18%), websites are 61 (6%), laws as many as 21 (2.09%), as many as 7 dictionaries (0.7%). The most frequently cited authors were Sugiyono with 44 citations and Sulistyo Basuki with 35 citations. The half-life of the citation literature was 4 years. The availability of cited literature was 811 (81%). For every year, literature has a different number in usage. There were some enhancements in the use of books, journals, and internet websites in 2017-2020.